Clinical review: Circulatory shock - an update: a tribute to Professor Max Harry Weil - Vincent, Jean-Louis (BioMed Central, 2012)
Circulatory shock is common and associated with high morbidity and mortality. Appropriate shock treatment relies on a good understanding of the pathophysiological mechanisms underlying shock. In this article, we provide an update on the description, classification, and management of shock states built on foundations laid by Dr Max Harry Weil, a key early contributor to this field.